2020
DOI: 10.1038/s41598-020-67256-3
|View full text |Cite
|
Sign up to set email alerts
|

Monosialoganglioside GM1 reduces toxicity of Ptx and increase anti-metastasic effect in a murine mammary cancer model

Abstract: Having demonstrated the ability of monosialoganglioside GM1 micelles as oncology drug transporter, this work focuses on evaluating its application in an in vivo system, studying the toxicity and antitumoral effect of GM1-Ptx micellar formulation. The maximum tolerated dose (MTD) obtained after intravenous administration of GM1-Ptx in mice was 55 mg/kg and the 50% lethal dose (LD50) was 70 mg/kg. This value is higher than those described for the commercial formulations TAXOL and ABRAXANE, with LD50 of 30 and 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Experiments were approved by the Committee on the Ethics of Animal Experiments of the Virgen Macarena y Virgen del Roci ́o University Hospitals, Seville, Spain (JSC-PIP-2018-01), and from the Ministry of Agricultura, Pesca y Desarrollo Rural (17/09/2018/143). The Reed and Munch method 62 was used to determine in vivo toxicity. Briefly, four female (RjHan/ AURA) golden Syrian hamsters per group (weight 80−100 g) were immunosuppressed with a dose of 140 mg/kg of cyclophosphamide 7 days before beginning with the treatments and then twice weekly at a dose of 100 mg/kg.…”
Section: -Chloro-n-(2-chloro-4-((3-(trifluoromethyl)benzyl)amino)phen...mentioning
confidence: 99%
“…Experiments were approved by the Committee on the Ethics of Animal Experiments of the Virgen Macarena y Virgen del Roci ́o University Hospitals, Seville, Spain (JSC-PIP-2018-01), and from the Ministry of Agricultura, Pesca y Desarrollo Rural (17/09/2018/143). The Reed and Munch method 62 was used to determine in vivo toxicity. Briefly, four female (RjHan/ AURA) golden Syrian hamsters per group (weight 80−100 g) were immunosuppressed with a dose of 140 mg/kg of cyclophosphamide 7 days before beginning with the treatments and then twice weekly at a dose of 100 mg/kg.…”
Section: -Chloro-n-(2-chloro-4-((3-(trifluoromethyl)benzyl)amino)phen...mentioning
confidence: 99%
“…GM1 accounts for the largest proportion and has been studied the most [10]. GM1 consists of a hydrophobic ceramide and a hydrophilic sugar chain and contains a molecule of sialic acid [11]. Studies revealed that GM1 can play a neuroprotective role in a variety of conditions, including the survival of nerve cells, the promotion of synaptic growth of nerve cells, the promotion of neuronal differentiation, and the protection of various types of nerve cells [12].…”
Section: Introductionmentioning
confidence: 99%